Efisiensi Digital Marketing Dalam Meningkatkan Penjualan Produksi Home Industry Malessa Fashion dan Craft di Kota Surakarta - Erlin Oktavia; Didit Purnomo (Universitas Muhammadiyah Surakarta, 2026)
This research aims to analyze the efficiency of digital marketing in increasing sales in the home industry of Malessa Fashion and Craft in Surakarta City. The research uses qualitative methods with data collection through interviews, observations, and direct experiences during the Merdeka Entrepreneur Internship program. The research results show that the implementation of digital marketing strategies through WhatsApp Business, Instagram, and Facebook platforms significantly increases sales. Special features such as business profiles, automated messages, feeds, stories, and direct interactions with customers have proven effective in expanding market reach, increasing audience engagement, and building customer trust. However, increasing audience engagement on Instagram still faces challenges due to the platform's algorithm and the quality of the uploaded content. Overall, digital marketing has become an effective solution for home-based industries to face increasingly tight and dynamic market competition.